Japan's higher education system and its benefits to meet some of the challenges in Saudi Arabia's universities - Al-Hodhaif, Fahad Saleh; Al-Hammad, Raya Abdullah; Al-Oraini, Nora Saleh; Al-Salamah, Roaa Ali (Journal of Educational and Psychological Sciences, 2022)
The aim of this research is to identify the higher education system in Japan and the benefits of it to meet some of the challenges in the Universities of the kingdom of Saudi Arabia, by knowing the general objectives of higher education in Japan, discovering the types of higher education institutions in it, knowing the methods of financing higher education, revealing the advantages of higher education, and also: One of the most prominent objectives of higher education in Japan is the equality of educational opportunities, and the most prominent types of institutions of higher education are universities and technological colleges, the most prominent methods of financing is government funding and private funding sources, the most prominent features are the excellence of technical and technical education, and the most prominent problems faced by: Functional coordination with various sectors in order to develop tests for functional inclinations, give universities in the kingdom the freedom to dispose of their financial income, and encourage private universities by reducing centralization in administrative decisions.
Keywords: Higher education in Japan; features; problems; benefits; Saudi Arabia